2010
DOI: 10.3171/2009.9.jns09577
|View full text |Cite
|
Sign up to set email alerts
|

Induction of panic attack by stimulation of the ventromedial hypothalamus

Abstract: Panic attacks are sudden debilitating attacks of intense distress often accompanied by physical symptoms such as shortness of breath and heart palpitations. Numerous brain regions, hormones, and neurotransmitter systems are putatively involved, but the etiology and neurocircuitry of panic attacks is far from established. One particular brain region of interest is the ventromedial hypothalamus (VMH). In cats and rats, electrical stimulation delivered to the VMH has been shown to evoke an emotional "panic attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 13 publications
5
74
0
2
Order By: Relevance
“…Knowing the fear circuit predominantly affected could help to develop psychotherapeutic and pharmacological interventions which will be more specific than interventions based on theoretical views that conceptualize fear as a unitary psychological construct. In humans, there is evidence that electrical stimulation of the dorsal part of the ventromedial nucleus of the hypothalamus (dmVMH) elicits a sensation of panic and impending death (Wilent, 2010) and that stimulation of the dorsolateral PAG causes a feeling of uncertainty and being chased by someone (Amano et al, 1982). Perhaps underlying panic attacks, which cause so much suffering to many people, is a circuit of predator fear.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the fear circuit predominantly affected could help to develop psychotherapeutic and pharmacological interventions which will be more specific than interventions based on theoretical views that conceptualize fear as a unitary psychological construct. In humans, there is evidence that electrical stimulation of the dorsal part of the ventromedial nucleus of the hypothalamus (dmVMH) elicits a sensation of panic and impending death (Wilent, 2010) and that stimulation of the dorsolateral PAG causes a feeling of uncertainty and being chased by someone (Amano et al, 1982). Perhaps underlying panic attacks, which cause so much suffering to many people, is a circuit of predator fear.…”
Section: Discussionmentioning
confidence: 99%
“…29 Hypothalamic DBS has been considered a possible therapeutic option for refractory obesity, panic disorder, and aggressive or disruptive behaviors in patients with mental impairment or brain damage. 31,113 For some of those conditions, encouraging results are becoming available in the literature.…”
mentioning
confidence: 92%
“…9,75 In 2010, Wilent et al reported panic attacks in response to stimulation of the VMH in a 50-year-old woman undergoing bilateral implantation of DBS leads into the lateral hypothalamus for the treatment of obesity. 113 The patient had a dramatic increase in anxiety, blood pressure, and heart rate, accompanied by hyperventilation and nausea. While stimulation of this area in either hemisphere led to the aforementioned response, stimulation appeared to be more effective at the center of the VMH.…”
mentioning
confidence: 99%
“…Confirming that stimulation of the VMH leads to undesirable effects, Wilent et al reported that DBS induced panic attacks in a graded manner during HFS of the VMH, demonstrating that its stimulation causes adverse psychogenic manifestations. 105 Since publication of these results, no additional trials involving DBS of the VMH have been reported.…”
Section: Past and Present Dbs Targets For Obesity Ventromedial Hypothmentioning
confidence: 99%